ANALISIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM UPAYA PENINGKATAN AKTIVITAS MAHASISWA TERHADAP SIKAP DEMOKRATIS PADA MATA KULIAH PENDIDIKAN KEWARGANEGARAAN - Seituni, Siti (Guidance and Counseling Study Program, Pattimura University, 2019)
The application of learning and the use of the proper learning model really need to be considered in order to help find out students' understanding of what is conveyed by the teacher. Problem Based Learning is a learning model that focuses on students or student center. The problem-based learning model has a way of dealing with problems in real life and is learning emphasizes investigative activities in solving problems. This study uses descriptive qualitative research method with qualitative descriptive phenomenological analysis techniques to describe broadly and deeply about the learning process when using Problem Based Learning model. By observing and examining the focus of reality or experience experienced by the object of research. The research object chosen in this study was STKIP PGRI Situbondo students who participate in the discussion class on citizenship education.